Prime Ministers and Rhetorical Governance - Grube, Dennis; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Prime Ministers in Westminister style democracies are forever talking to and communicating with the electorate. This ground-breaking book explores and analyses the uses of political rhetoric by Prime Ministers to explore patterns of communication and shows that the manner in which they talk to the electorate is central to day-to-day governance.
Keywords: Science; Science; Science, general